"Never Let a Good Crisis Go to Waste": Can International Law Seize the Advantage?. (2021) - Daudet, Yves
Abstract : Some international crises are circumscribed, others are more diffuse, sometimes of varying intensity depending on the region. But, at the end of the day, all regions might be impacted according to an uncertain timetable. This is the case, for example, with terrorism, cybersecurity, the migration crisis, and the climate crisis, which is one aspect of environmental damage that intersects with the health crisis. Some are latent and marked by sudden outbreaks, such as terrorism or the Islamic State's criminal operations. Others are set to worsen, such as the migration crisis, which today is probably small compared to what it will become. We must also think about financial or economic crises, cybersecurity breaches, misuse of new technologies and social networks, and, importantly, the painful experience of the January 2021 democratic crisis in the United States. But the current COVID-19 health crisis is the crisis that occupies everyone's mind today.